Not Your Everyday Objects - Rychter, Marcin (Eidos. A Journal for Philosophy of Culture, 2024)
Preview: /Review: Graham Harman and Christopher Witmore, Objects Untimely: Object-Oriented Ontology and Archaeology, (Cambridge and Hoboken: Polity Press, 2023), 240 pages./ This is a very unusual book and it is so in several different respects. Firstly, it is co-authored and that already makes it a rare bird in contemporary philosophical output. Secondly, the author duo represent different academic disciplines. Graham Harman is a philosopher devoted to developing and promoting his own metaphysical system, which he dubbed Object Oriented Ontology (OOO), whereas Christopher Witmore is an archaeologist and classicist focused on the material heritage of Ancient Greece. It is not just the fact that the book is co-authored by people with different professional backgrounds that makes it unique, but also that both authors themselves stand apart within their own fields. With his consistent focus on creating and constantly improving his own “theory of everything” while at the same time refusing to conform to either of the dominant trends in both continental and analytical philosophy, Harman is an exceptional figure in the landscape of contemporary philosophy. Also, Witmore – who displays a lot of interest in the abstract problems of methodological, philosophical and anthropological nature – is far from being a “typical” archaeologist of the day. Finally, the main topic of the book, which is on the nature and possible ways of conceptualizing time, is not often explicitly addressed in the recent literature within these fields – despite its undoubtedly fundamental significance for both philosophy and archaeology.